Quantitative 177Lu-DOTATATE SPECT/CT is predictive of 6-month PRRT morphological response in midgut neuroendocrine tumors: a pilot study - Iness Megherbi; Christopher Hoog; Marine Perrier; Hedia Brixi; Guillaume Cadiot; Christine Hoeffel-Fornes; David Morland (EJNMMI Research)
Abstract Background peptide receptor radionuclide therapy with 177Lu-DOTATATE has become an established second-line treatment for patients with advanced small intestine neuroendocrine tumors (siNET). Treatment efficacy is assessed several months after the end of treatment and is based on RECIST criteria. Post-therapy scintigraphy (PTS) can be performed after each cycle, but its value in early response assessment is debated particularly given the lack of quantification available in clinical routine. New quantification modules are now available, enabling automatic SUV calculation. The main goal of this study is to assess the value of the evolution of SUV between the first (C1) and the second (C2) cycle on quantitative PTS in predicting response to treatment. All patients with siNET referred to our center for treatment with 177Lu-DOTATATE were included. The SUVmax of the lesion with the greatest uptake was measured on PTS SPECT/CT at C1 and C2. ∆SUVmax was calculated. Linear regression between ∆SUVmax and 6-month RECIST percentage was used. Relative changes in tumor metabolic volume (MTV) were also studied along with clinical parameters. Results twelve consecutive patients with progressive metastatic siNET were included. One patient showed partial response at 6 months, the other were considered as stable disease. Linear regression showed that 6-month RECIST percentage and ∆SUVmax were strongly correlated with the following regression formula: 6-month RECIST = -0.05 + 0.36 x ∆SUVmax (p < 0.001). ∆MTV was not predictive of response. Conclusion we report a significant link between PTS ∆SUVmax and 6-month RECIST percentage in patients with siNET. Quantitative imaging would thus enable the prediction of 6-month response of 177Lu-DOTATATE as early as C2. These results need to be confirmed on a larger population.